Study oil thermal-physical properties for nanocellulose nanoparticles for sae40 engine oil for tribological behaviour - Norazmira Wati, Awang (2021)
Wear and friction are inevitable problems in engineering applications which causes reduced efficiency in mechanical systems. One solution to this problem is to use a lubricant that can reduce friction and wear to a minimum, resulting in increased efficiency. The development of efficient lubricant additives has received significant industrial and academic attention for tribological properties enhancement and increased thermal conductivity. In general, nano-sized particles dispersed in the lubricants, known as nano lubricants, are used in mechanical systems to reduce heat and friction effectively. Furthermore, new environmental regulations will encourage the usage of lubricants with greener lubrication technologies. Addressing this issue requires the use of lubricants that conforms to environmental standards while maintaining excellent lubrication performance. Therefore, as a new green additive, this study intends to investigate the dispersion of Cellulose Nanocrystals (CNCs) nanoparticles in engine oils. The purpose of this study is to investigate the effect of CNCs added SAE 10 W 40 (SAE 40) engine oil on the thermal-physical properties and tribological behaviour. The optimum design was analysed to indicate which parameters are statistically significant for obtaining a low coefficient of friction (COF) and low wear with CNCs added on SAE 40 engine oil. CNCs nanoparticles were dispersed in the baseline engine oil using the two-step method preparation. The two-step method preparation with a low volume concentration in the range of 0.1 % to 0.9 %., was used in the preparation of CNC’s based engine oil. Thermal-physical properties such as thermal conductivity, kinematic viscosity, viscosity index (VI), density, and specific heat were measured for all volume concentrations. Meanwhile, tribological properties of CNCs added on SAE 40 engine oil were evaluated for different sliding speeds, applied load, and temperatures. The friction-wear test involves making linear reciprocating movements like a cylinder-piston ring pair operating under actual conditions. To optimize the tribology performance parameters, the Response Surface Methodology (RSM) based on the Box-Behnken design was adopted. Stability evaluation showed CNCs added SAE 40 engine oil was stable throughout the study, and after 60 days, very little sedimentation was observed. Thermal conductivity and specific heats of CNCs added SAE 40 engine oil had increased with the volume concentration. The tribology properties observation with optimal conditions of coefficient of friction (COF) and wear rates were found at 0.1% volume concentration, effective in improving the anti-wear and scuffing resistance via the formation of self-laminating protective films. The surface morphology of the specimens revealed that the CNCs added SAE 40 engine oil produced a smoother surface. The optimization results yielded an optimum COF and surface wear rate from 500 rpm, 78.71 N, and 0.1 % volume concentrations with the highest desirability of 75.4 %. The presence of CNCs nanoparticles as an additive in SAE 40 engine oils samples ultimately improved the tribological performances. Base oil containing 0.1% CNC has excellent tribological properties, including the lowest COF and the highest wear resistance under all lubrication conditions. Based on the findings of this study, it can be concluded that cellulose nanocrystal is a promising lubricant additive, especially for green applications